Resilience to climate shocks in the tropics. (30th September 2020) - Hirons, Mark; Beauchamp, Emilie; Whitfield, Stephen; Conway, Declan; Asare, Rebecca; Malhi, Yadvinder
Abstract: This focus collection on resilience to climate shocks in the tropics draws together 16 papers that predominantly examine the impacts of, and responses to, the 2015/2016 El Niño-Southern Oscillation event, in a range of contexts. This introductory synthesis contextualises the collection of papers by reviewing important concepts and highlighting some important insights that emerge from the collection. The papers in this collection collectively highlight: the value of longitudinal and interdisciplinary research in understanding both the roots of, and responses to, resilience challenges; the critical interaction between climatic and land-use changes; and the ways in which governance arrangements underpin societal decision-making across a range of scales and contexts to shape resilience.